Ferromagnetic transition in diluted magnetic semiconductors - Dietl, T. (Condensed Matter Physics, 1999)
A summary is given of recent theoretical works on effects of the Ruderman-
Kittel-Kasuya-Yosida (RKKY) interaction between the localized spins in
various dimensionality systems of doped diluted magnetic semiconductors (DMS). Since this interaction is long-range, its inﬂuence on the temperature and magnetic ﬁeld dependencies of magnetization and spin
splitting of the bands is evaluated in the mean ﬁeld approximation,
but by taking into consideration disorder-modiﬁed carrier-carrier interactions. Theoretical evaluations show that the hole densities, which can
presently be achieved, are sufﬁciently high to drive a paramagnetic-
ferromagnetic phase transition in bulk and modulation-doped structures of
II-VI DMS. The results of recent magnetooptical studies on MBE-grown
samples, containing a single, modulation-doped, 8 nm quantum well of
Cd₁₋xMnxTe/Cd₁₋y₋zMgyZnzTe:N are shown to corroborate the theoretical expectations. These studies reveal the presence of a ferromagnetic
transition induced by the two-dimensional hole gas. The transition occurs
between 1.8 and 2.5 K, depending on the Mn concentration x, in agreement
with the theoretical model. Зроблено огляд недавніх теоретичних робіт про вплив взаємодії
Рудермана-Кіттеля-Касуї-Іоміди між локалізованими спінами у системах різної вимірності в розведених магнітних напівпровідниках
(РМН). Оскільки ця взаємодія далекосяжна, її вплив на температурну і польову залежності намагніченості і спінове розщеплення зон
оцінюється в наближенні середнього поля, беручи до уваги змінену
безладом взаємодію носій-носій. Теоретичні оцінки показують, що
експериментально досяжні густини дірок достатньо високі для того, щоб спричинити фазовий перехід парамагнетик-феромагнетик у
тривимірних модульованих структурах II–VI РМН. Показано, що результати теоретичних обчислень підтверджуються недавніми магнетооптичними дослідженнями вирощених методом НВЕ зразків
Cd₁₋xHnxTe/Cd₁₋₄₋₇HgyZnz:N, що містять одну модульовану квантову яму глибиною 8 nm. Ці дослідження свідчать про наявність феромагнітного переходу, спричиненого двовимірним дірковим газом.
Перехід відбувається при температурі між 1.8 і 2.5 K, залежно від концентрації марганцю x, що узгоджується з теоретичною моделлю.